Estudio del proceso de fabricación de perfiles laminados en caliente, para el control estadístico del producto en la empresa Novacero S.A. - Herrera Astudillo, Evelin Yajaira (2020)
In the “Novacero S.A” Company, Lasso Factory, different products are manufactured that are useful for construction, among them are the hot rolled profiles such as angles, plates, round, square bars and TEE´s, where the production line Train 2 of rolling is responsible for the manufacture of these products. Throughout its development, this area has presented several disadvantages that affect the productivity of the area; among them are the nonconformities, which derive in product defects that do not meet the quality standards required by the norm and the company, for this reason, a study was conducted to determine the best quality tool to reduce losses due to nonconformities and reprocessing. This study consisted in collecting data of the width and thickness angles of different measures that were analyzed with Minitab software and through process capability graphs, histograms, parentheses identified which are the products that are generally out of specification what mentions the standard INNEN 2224 where it was determined that the angle of 100 is the one that presents more problems, being “the dimensions out of specification,” one of the defects with the highest number of nonconformities. In addition, through the limits modification proposal of the control chart, it was possible to control different factors that directly and indirectly affected the angle manufacturing process in the rolling mill train 2 area, being the direction of the stands and its calibration the main cause for the finished product to present visual and dimensional defects, as well as, it is also important to take initial data to be able to control the continuation of the process.